The Developement of Learning Method “Imagination Box”: An Effective and Efficient Method to Evaluate Student’s Understanding - Sumarsono, Adi; Mubarokah, Fitriani (Jurnal Pendidikan Progresif, 2019)
The Developement of Learning Method “Imagination Box”: An Effective and Efficient Method to Evaluate Student’s Understanding. Objectives: This study aims to develop effective and efficient learning method in order to evaluate student’s understanding in the theory of physical education, sport, health, and recreation equiped with assesment isntrument. Method: This study is research and development which is addopted from ADDIE. Datas analysis thecniques are quantitative and qualitative. Quantitative data analysis technique used descriptive statistical analysis and qualitative data analysis including analysis of instrument feasibility, analysis of instrument trials and analysis of the results of the conversion criteria of the instruments developed. Findings: The information aspect of the method developed is valid with a mean score of 3.2-3.6, the average performance aspect is high with score of 3.5-3.7, and the efficiency aspect of the method is high with score of 3.3-3.5. Results: The learning method “Imagination Box” which is equipped with the assessment instrument produced is feasible to be implemented and become variation of the learning method for teacher.Kata kunci:imagination box, ADDIE, student’s understanding DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201908